Modelling and simulation of a 1.6 Tb/s optical system based on multi-diagonal code and optical code-division multiple-access - Thanaa Hussein, Abd.; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Hilal Adnan, Fadhil, Dr.; Junita, Mohd Nordin; Mohamad Naufal, Mohamad Saad, Prof. Madya Dr. (Institute of Physical Optics, 2013)
Link to publisher's homepage at http://www.ifo.lviv.ua/